Analisis Modifikasi Algoritma Kriptografi Klasik Menggunakan Algoritma Blum-Micali Generator - Aripin, Soeb; Syahrizal, Muhammad (STIKOM Tunas Bangsa Pematangsiantar, 2022)
Classical cryptography is the science of securing secret messages (plaintext) into disguised messages (ciphertext) in which each character is changed. The process of converting plaintext into ciphertext is called encryption, while the reverse process is called decryption. However, this classical crypto algorithm can still be solved using the Kasiski method, due to the mathematically regular pattern of repeating keywords. Therefore, in order not to be easily solved, another method is needed, namely by modifying the Caesar Cipher and Vigenere Cipher cryptographic algorithms. Therefore, to strengthen the security of the classical cryptography algorithm, it is necessary to carry out a modification process using an algorithm that is able to change the complexity of the encoding by using a randomization algorithm. By including a randomization algorithm, it is considered that it can eliminate the possibility of attackers guessing the results by knowing the algorithm used. The randomization algorithm used is the Blum-Micali Generator algorithm. The purpose of using the Blum-Micali Generator algorithm is that the encryption process is randomized so that the encryption results obtained are more difficult to guess, making it difficult for cryptanalysts to read the message or information